Optical Properties of Sodium Chloride Solution within the Spectral Range from 300 to 2500 nm at Room Temperature. Issue 5 (May 2015) - Li, Xingcan; Liu, Linhua; Zhao, Junming; Tan, Jianyu
The optical properties of sodium chloride (NaCI) solution were experimentally determined by double optical pathlength transmission method in the spectral range from 300 to 2500 nm at the NaCl concentration range from 0 to 360 g/L. The results show that the refractive index of NaCl solution increases with NaCl concentrations and correlates nonlinearly with the concentration of NaCl solution. The absorption index of NaCl solution increases with NaCl concentrations in the visible spectral range of 300-700 nm, but varies little in the near-infrared spectral range of 700-2500 nm at room temperature. For the sake of applications, the fitted formulae of the refractive index and absorption index of NaCl solution as a function of wavelength and NaCl concentration are presented.